Copper alloy profiled strip, assembly for electronic and electric equipment, terminal, bus bar, lead frame, and heat dissipation substrate

CN118339317BActive Publication Date: 2026-10-30MITSUBISHI MATERIALS CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202280072673.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-12-28
Filing Date
2022-12-27
Publication Date
2026-10-30
Estimated Expiration
2042-12-27

AI Technical Summary

Technical Problem

[0012]在此,这些材料通过溶质元素的添加来改善耐热特性,但对于具备厚度互不相同的厚部及薄部的铜合金异型带材而言,厚部及薄部的材料组织的组织结构会容易不同,厚部及薄部的强度和耐热性等特性容易产生差异,有可能无法在高温环境下稳定地使用

Benefits of technology

[0036]该构成的散热基板由于使用上述铜合金异型带材制造,因此即使在高温环境下也能够发挥优异的特性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0004814574610000161
    Figure GDA0004814574610000161
  • Figure GDA0004814574610000171
    Figure GDA0004814574610000171
  • Figure GDA0004814574610000181
    Figure GDA0004814574610000181
Patent Text Reader

Abstract

Provided is a copper alloy profiled strip having high electrical conductivity and excellent heat resistance, which has a thick portion and a thin portion having different thicknesses in a cross section orthogonal to a length direction, wherein the copper alloy profiled strip has a composition in which the content of Mg is in a range of more than 10 mass ppm and less than 1.2 mass %, the content of P is in a range of 0 mass ppm or more and 200 mass ppm or less, and the remainder is Cu and inevitable impurities, the electrical conductivity is 48 % IACS or more, the heat resistance temperature T1 of the thick portion is 260 °C or more, the heat resistance temperature T2 of the thin portion is 240 °C or more, and 0.9 < T1 / T2 < 1.25, the small-angle grain boundary ratio B1 of the thick portion is 80 % or less, the small-angle grain boundary ratio B2 of the thin portion is 80 % or less, and 0.8 < B1 / B2 < 1.2, and the area ratio of crystals having a crystal orientation within 10° with respect to the Goss orientation {011} <100> is 1 % or more in each of the thick portion and the thin portion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a copper alloy profiled strip suitable for electronic and electrical equipment components such as terminals, busbars, lead frames, and heat dissipation substrates, and electronic and electrical equipment components, terminals, busbars, lead frames, and heat dissipation substrates made from the copper alloy profiled strip.

[0002] This application claims priority based on Japanese Patent Application No. 2021-214036, filed on December 28, 2021, the contents of which are incorporated herein by reference. Background Technology

[0003] In the past, highly conductive copper or copper alloys were used in electronic and electrical equipment components such as terminals, busbars, lead frames, and heat sinks.

[0004] In this context, with the increasing current of electronic devices or electrical equipment, in order to reduce current density and dissipate heat caused by Joule heating, it is also an attempt to increase the size and thickness of electronic and electrical components used in these electronic devices or electrical equipment.

[0005] To handle high currents, pure copper materials such as oxygen-free copper, which have excellent conductivity, are used in the components of the aforementioned electronic and electrical equipment. However, with the heat generated during power-on or the increasing temperature of the operating environment, copper materials with excellent heat resistance (heat resistance means that the hardness is difficult to decrease at high temperatures) are required. However, pure copper materials have poor properties in these aspects, making them unusable in high-temperature environments.

[0006] Therefore, Patent Document 1 discloses a copper rolled plate containing Mg in the range of 0.005% by mass or more and less than 0.1% by mass.

[0007] Regarding the copper rolled sheet described in Patent Document 1, since it has a composition containing Mg in the range of 0.005% by mass and less than 0.1% by mass, with the remainder consisting of Cu and unavoidable impurities, it is possible to improve the strength and heat resistance without significantly reducing the conductivity by dissolving Mg in the copper matrix.

[0008] Furthermore, as raw materials for the components of the aforementioned electronic and electrical equipment, copper alloy profiled strips with thick and thin portions of different thicknesses on a cross section orthogonal to the length direction are used, for example, as disclosed in Patent Documents 2 and 3.

[0009] Patent Document 1: Japanese Patent Application Publication No. 2016-056414(A)

[0010] Patent Document 2: Japanese Patent Application Publication No. 2007-039735(A)

[0011] Patent Document 3: Japanese Patent Application Publication No. 2009-009887 (A)

[0012] Here, these materials improve heat resistance by adding solute elements. However, for copper alloy profiled strips with different thicknesses, the microstructure of the thick and thin sections may be different, and the strength and heat resistance of the thick and thin sections may vary, which may prevent them from being used stably in high-temperature environments. Summary of the Invention

[0013] The invention was made in view of the foregoing circumstances, and its purpose is to provide a copper alloy profiled strip with properties such as strength and heat resistance that are not easily different between the thick and thin portions and can be used stably in high-temperature environments, and components, terminals, busbars, lead frames and heat dissipation substrates for electronic and electrical equipment made of the copper alloy profiled strip.

[0014] To address this issue, the copper alloy profiled strip of the present invention has thick and thin sections of varying thicknesses on a cross-section orthogonal to the length direction. The copper alloy profiled strip is characterized by having a Mg content exceeding 10 ppm by mass and below 1.2 ppm by mass, a P content exceeding 0 ppm by mass and below 200 ppm by mass, and the remainder consisting of Cu and unavoidable impurities. Its electrical conductivity is 48% IACS or higher. The heat resistance temperature T1 of the thick section is 260°C or higher, and the heat resistance temperature T2 of the thin section is 240°C or higher, with 0.9 < T1 / T2 < 1.25. Using the EBSD method, in the rolling surface (ND plane, normal direction), measurement points with a CI value below 0.1 are excluded at 0.25 μm intervals, for a length of 10000 μm. 2 The above measurements were used to analyze the orientation difference of each grain. Grain boundaries were defined between adjacent measurement points with an orientation difference of 15° or more. The average grain size A was calculated using area fraction. Measurements were performed at intervals less than 1 / 10 of the average grain size A, covering more than 1000 grains, with a total size of 10000 μm in multiple fields of view. 2 Of the measured areas above, measurement points with a CI value below 0.1 as analyzed by the data analysis software OIM were excluded. The length of the small-angle grain boundaries and subgrain boundaries between adjacent measurement points with an orientation difference of 2° or more but less than 15° was defined as L. LB The length of the large-angle grain boundary between adjacent measurement points with an orientation difference exceeding 15° is defined as L. HB And let the length ratio of the small-angle grain boundary and the subgrain boundary be defined as the small-angle grain boundary ratio B = L. LB / (LLB +L HB When the ratio of small-angle grain boundaries B1 in the thick portion is 80% or less, the ratio of small-angle grain boundaries B2 in the thin portion is 80% or less, and 0.8 < B1 / B2 < 1.2, the area ratio of crystals with a crystal orientation of less than 10° relative to the Goss orientation {011} < 100> is 1% or more in both the thick portion and the thin portion.

[0015] According to the copper alloy profiled strip with this composition, since the Mg content is in the range of more than 10 ppm by mass and less than 1.2% by mass, and the P content is in the range of more than 0 ppm by mass and less than 200 ppm by mass, the heat resistance can be sufficiently improved by the solid dissolution of Mg in the copper matrix.

[0016] Furthermore, since its conductivity is above 48% IACS, it can suppress heat generation when energized, making it suitable as a raw material for electronic and electrical equipment components such as terminals, busbars, lead frames, and heat dissipation substrates.

[0017] Furthermore, the heat resistance temperature T1 of the thick portion is above 260°C, and the heat resistance temperature T2 of the thin portion is above 240°C, and 0.9 < T1 / T2 < 1.25. Therefore, the heat resistance is sufficiently excellent, and the difference in heat resistance between the thick and thin portions is small, which steadily improves the overall heat resistance of the copper alloy profiled strip.

[0018] Furthermore, since the crystal structure is controlled in such a way that the ratio of small-angle grain boundaries and the area ratio of Goss-oriented crystals in the thick and thin portions are within the above-mentioned ranges, recovery or recrystallization caused by dislocation movement is less likely to occur, and the heat resistance of the thick and thin portions can be sufficiently improved.

[0019] In the copper alloy profiled strip of the present invention, preferably, among the unavoidable impurities, the content of S is 10 ppm by mass or less, the content of Se is 5 ppm by mass or less, the content of Te is 5 ppm by mass or less, the content of Sb is 5 ppm by mass or less, the content of Bi is 5 ppm by mass or less, the content of As is 5 ppm by mass or less, and the total content of S, Se, Te, Sb, Bi and As is 24 ppm by mass or less.

[0020] In this case, since the contents of the elements that form compounds with Mg, namely S, Se, Te, Sb, Bi, and As, are specified as described above, Mg can be reliably dissolved, thereby further improving the heat resistance.

[0021] Furthermore, in the copper alloy profiled strip of the present invention, the content of Ag is preferably in the range of 5 ppm by mass or more and 20 ppm by mass or less.

[0022] In this case, since Ag is present in the range described above, Ag segregates near the grain boundaries, and grain boundary diffusion is suppressed, thereby further improving heat resistance.

[0023] Furthermore, in the copper alloy profiled strip of the present invention, it is preferable that the Vickers hardness H1 of the thick portion is 70Hv or higher, the Vickers hardness H2 of the thin portion is 75Hv or higher, and 0.7 < H1 / H2 < 1.2.

[0024] In this case, since the Vickers hardness H1 of the thick portion is 70Hv or higher and the Vickers hardness H2 of the thin portion is 75Hv or higher, and the Vickers hardness ratio H1 / H2 is 0.7 < H1 / H2 < 1.2, the strength is excellent, and the strength difference between the thick and thin portions is small, enabling stable use.

[0025] Furthermore, it is preferable that the surface of the copper alloy profiled strip of the present invention has a metal plating layer.

[0026] In this case, due to the metallic coating on the surface, it is particularly suitable as a raw material for components of electronic and electrical equipment such as terminals, busbars, lead frames, and heat dissipation substrates.

[0027] The electronic and electrical equipment component of the present invention is characterized in that it is composed of the aforementioned copper alloy profiled strip. Furthermore, the electronic and electrical equipment component of the present invention includes terminals, busbars, lead frames, heat sinks, etc.

[0028] Because the electronic and electrical equipment components are manufactured using the aforementioned copper alloy profiled strip, they exhibit excellent properties even in high-temperature environments.

[0029] The terminal of the present invention is characterized in that it is made of the aforementioned copper alloy profiled strip.

[0030] Because the terminals are made using the aforementioned copper alloy profiled strip, they exhibit excellent properties even in high-temperature environments.

[0031] The busbar of the present invention is characterized in that it is made of the aforementioned copper alloy profiled strip.

[0032] Because the busbar is made using the aforementioned copper alloy profiled strip, it can exhibit excellent properties even in high-temperature environments.

[0033] The lead frame of the present invention is characterized in that it is made of the aforementioned copper alloy profiled strip.

[0034] Because the lead frame is made using the aforementioned copper alloy profiled strip, it exhibits excellent properties even in high-temperature environments.

[0035] The heat dissipation substrate of the present invention is characterized in that it is composed of the aforementioned copper alloy profiled strip.

[0036] Because the heat dissipation substrate is made using the aforementioned copper alloy profiled strip, it can exhibit excellent properties even in high-temperature environments.

[0037] According to the present invention, a copper alloy profiled strip with properties such as strength and heat resistance that are not easily different between thick and thin sections and can be used stably in high-temperature environments is provided, as well as components, terminals, busbars, lead frames, and heat dissipation substrates for electronic and electrical equipment made of the copper alloy profiled strip. Attached Figure Description

[0038] Figure 1 This is a cross-sectional diagram illustrating the copper alloy profiled strip of this embodiment.

[0039] Figure 2 This is a flowchart of the manufacturing method of the copper alloy profiled strip according to this embodiment. Detailed Implementation

[0040] Hereinafter, a copper alloy profiled strip according to an embodiment of the present invention will be described with reference to the accompanying drawings.

[0041] The copper alloy profiled strip of this embodiment is most suitable as a raw material for components used in electronic and electrical equipment such as terminals, busbars, lead frames, and heat sinks.

[0042] like Figure 1 As shown, the copper alloy profiled strip 10 of this embodiment has a thick portion 11 and a thin portion 12 with different thicknesses on a cross section orthogonal to the length direction.

[0043] Furthermore, the ratio t1 / t2 of the thickness t1 of the thick portion 11 to the thickness t2 of the thin portion 12 is preferably 8 or less, and more preferably 6 or less.

[0044] The copper alloy profiled strip 10 of this embodiment has a Mg content in the range of more than 10 ppm by mass and less than 1.2% by mass, a P content in the range of more than 0 ppm by mass and less than 200 ppm by mass, and the remainder is Cu and unavoidable impurities.

[0045] In the copper alloy profiled strip 10 of this embodiment, preferably, among the unavoidable impurities, the content of S is 10 ppm by mass or less, the content of Se is 5 ppm by mass or less, the content of Te is 5 ppm by mass or less, the content of Sb is 5 ppm by mass or less, the content of Bi is 5 ppm by mass or less, the content of As is 5 ppm by mass or less, and the total content of S, Se, Te, Sb, Bi and As is 24 ppm by mass or less.

[0046] Furthermore, in the copper alloy profiled strip 10 of this embodiment, the Ag content can be in the range of 5 ppm by mass or more and 20 ppm by mass or less.

[0047] Furthermore, the copper alloy profiled strip 10 of this embodiment has a conductivity of 48% IACS or higher.

[0048] Furthermore, in the copper alloy profiled strip 10 of this embodiment, the heat resistance temperature T1 of the thick portion 11 is 260°C or higher, the heat resistance temperature T2 of the thin portion 12 is 240°C or higher, and 0.9 < T1 / T2 < 1.25.

[0049] Furthermore, in the copper alloy profiled strip 10 of this embodiment, the EBSD method is used to exclude measurement points with a CI value of 0.1 or less in the rolling surface, i.e., the ND (Normal direction) surface, with a measurement interval of 0.25 μm, for a length of 10000 μm. 2 The above measurements were used to analyze the orientation difference of each grain. Grain boundaries were defined between adjacent measurement points with an orientation difference of 15° or more. The average grain size A was calculated using area fraction. Measurements were performed at intervals less than 1 / 10 of the average grain size A, covering more than 1000 grains, with a total size of 10000 μm in multiple fields of view. 2 Of the measured areas above, measurement points with a CI value below 0.1 as analyzed by the data analysis software OIM were excluded. The length of the small-angle grain boundaries and subgrain boundaries between adjacent measurement points with an orientation difference of 2° or more but less than 15° was defined as L. LB The length of the large-angle grain boundary between adjacent measurement points with an orientation difference exceeding 15° is defined as L. HB And let it be set as the ratio of the lengths of small-angle grain boundaries and subgrain boundaries, i.e., the small-angle grain boundary ratio B = L. LB / (L LB +L HB When the ratio of small-angle grain boundaries B1 in the thick portion 11 is less than 80%, the ratio of small-angle grain boundaries B2 in the thin portion 12 is less than 80%, and 0.8 < B1 / B2 < 1.2.

[0050] Furthermore, in the copper alloy profiled strip 10 of this embodiment, the area ratio of crystals having a crystal orientation of 10° or less relative to the Goss orientation {011}<100> is 1% or more in both the thick portion 11 and the thin portion 12.

[0051] Furthermore, in the copper alloy profiled strip 10 of this embodiment, it is preferable that the Vickers hardness H1 of the thick portion 11 is 70Hv or higher, the Vickers hardness H2 of the thin portion 12 is 75Hv or higher, and 0.7 < H1 / H2 < 1.2.

[0052] Here, the reasons for specifying the composition, various properties, and crystal structure of the copper alloy profiled strip 10 in this embodiment as described above will be explained.

[0053] (Mg)

[0054] Mg is an element that has the following effect: by being dissolved in the matrix phase of copper, it can improve strength and heat resistance without significantly reducing electrical conductivity.

[0055] Here, when the Mg content is below 10 ppm by mass, it may not be able to fully exert its effect. On the other hand, when the Mg content is above 1.2% by mass, the conductivity will decrease, and it may not be able to be stably used as a raw material for components of electronic and electrical equipment.

[0056] Based on the above, in this embodiment, the Mg content is set within a range of more than 10 ppm by mass and less than 1.2 ppm by mass.

[0057] Here, in order to further improve the heat resistance temperature, the Mg content is preferably set to 20 ppm by mass or more, more preferably 30 ppm by mass or more, and even more preferably 40 ppm by mass or more.

[0058] Furthermore, in order to further suppress the decrease in conductivity, the content of Mg is preferably set to 1.0% by mass or less, more preferably 0.8% by mass or less, more preferably 0.6% by mass or less, and even more preferably 0.4% by mass or less.

[0059] (P)

[0060] P is an element that improves castability and can be added to increase productivity. On the other hand, if added in excess, it can react with Mg to form compounds, which may reduce the solid solution effect of Mg.

[0061] Based on the above, in this embodiment, the content of P is set within the range of 0 ppm by mass and 200 ppm by mass.

[0062] In order to further reliably exert the solid solution effect of Mg, the content of P is preferably set to 160 ppm by mass or less, more preferably 120 ppm by mass or less, more preferably 80 ppm by mass or less, and even more preferably 60 ppm by mass or less.

[0063] (S, Se, Te, Sb, Bi, As)

[0064] The elements mentioned above, such as S, Se, Te, Sb, Bi, and As, are typically prone to incorporating into copper alloys. Furthermore, these elements readily react with Mg to form compounds, potentially reducing the solid solution effect of trace amounts of added Mg. Therefore, the content of these elements needs to be strictly controlled.

[0065] Therefore, in this embodiment, it is preferable to limit the content of S to less than 10 ppm by mass, the content of Se to less than 5 ppm by mass, the content of Te to less than 5 ppm by mass, the content of Sb to less than 5 ppm by mass, the content of Bi to less than 5 ppm by mass, and the content of As to less than 5 ppm by mass.

[0066] Furthermore, it is preferable to limit the total content of S, Se, Te, Sb, Bi and As to below 24 ppm by mass.

[0067] Furthermore, the content of S is more preferably 9 ppm by mass or less, and even more preferably 8 ppm by mass or less.

[0068] The content of Se is more preferably 4 ppm by mass or less, and even more preferably 2 ppm by mass or less.

[0069] The Te content is more preferably 4 ppm by mass or less, and even more preferably 2 ppm by mass or less.

[0070] The Sb content is more preferably 4 ppm by mass or less, and even more preferably 2 ppm by mass or less.

[0071] The content of Bi is more preferably 4 ppm by mass or less, and even more preferably 2 ppm by mass or less.

[0072] The content of As is more preferably 4 ppm by mass or less, and even more preferably 2 ppm by mass or less.

[0073] Furthermore, the total content of S, Se, Te, Sb, Bi and As is more preferably 20 ppm by mass or less, and even more preferably 16 ppm by mass or less.

[0074] (Ag: 5 ppm or more by mass and 20 ppm or less by mass)

[0075] Ag is almost insoluble in the Cu matrix within the typical operating temperature range of electronic and electrical equipment, below 250°C. Therefore, trace amounts of Ag added to copper segregate near the grain boundaries. This hinders atomic movement at the grain boundaries, suppresses grain boundary diffusion, and thus improves heat resistance.

[0076] Here, when the Ag content is 5 ppm by mass or higher, its effect can be fully exerted. On the other hand, when the Ag content is 20 ppm by mass or lower, conductivity can be ensured and the increase in manufacturing costs can be suppressed.

[0077] Based on the above, in this embodiment, the content of Ag is set within the range of 5 ppm by mass or more and 20 ppm by mass or less.

[0078] Here, in order to further improve heat resistance, the Ag content is preferably set to 6 ppm by mass or more, more preferably 7 ppm by mass or more, and even more preferably 8 ppm by mass or more. Furthermore, in order to reliably suppress the decrease in conductivity and the increase in cost, the Ag content is preferably set to 18 ppm by mass or less, more preferably 16 ppm by mass or less, and even more preferably 14 ppm by mass or less.

[0079] In addition, when Ag is intentionally omitted, the Ag content can be lower than 5 ppm by mass.

[0080] (Other unavoidable impurities)

[0081] Other unavoidable impurities besides the elements mentioned above include Al, B, Ba, Be, Ca, Cd, Cr, Sc, rare earth elements, V, Nb, Ta, Mo, Ni, W, Mn, Re, Ru, Sr, Ti, Os, Co, Rh, Ir, Pb, Pd, Pt, Au, Zn, Zr, Hf, Hg, Ga, In, Ge, Y, Tl, N, Si, Sn, and Li. These unavoidable impurities can be present within a range that does not affect the properties.

[0082] Here, these unavoidable impurities may reduce conductivity, so the total amount is preferably 0.1% by mass or less, more preferably 0.05% by mass or less, even more preferably 0.03% by mass or less, and even more preferably 0.01% by mass or less.

[0083] Furthermore, the content of each of these unavoidable impurities is preferably 10 ppm by mass or less, more preferably 5 ppm by mass or less, and even more preferably 2 ppm by mass or less.

[0084] (Small-angle grain boundary ratio)

[0085] Within grain boundaries, small-angle grain boundaries and subgrain boundaries are regions with high dislocation density introduced during processing. Therefore, if the ratio of the lengths of small-angle grain boundaries and subgrain boundaries, i.e., the small-angle grain boundary ratio B = L, then... LB / (L LB +L HBIf the temperature is too high, high-speed diffusion of atoms via dislocations can easily occur, leading to recrystallization and softening at high temperatures, potentially compromising heat resistance. Furthermore, since the thick portion 11 and the thin portion 12 are used in the same temperature environment, it is required that the heat resistance of the thick portion 11 and the thin portion 12 is not significantly different.

[0086] Therefore, in this embodiment, the small tilt angle grain boundary ratio B1 of the thick portion 11 is set to 80% or less, and the small tilt angle grain boundary ratio B2 of the thin portion 12 is set to 80% or less.

[0087] Furthermore, the ratio of the small-angle grain boundary ratio B1 of the thick portion 11 to the small-angle grain boundary ratio B2 of the thin portion 12 is set to B1 / B2 as 0.8 < B1 / B2 < 1.2.

[0088] Here, the ratio of small-angle grain boundaries B1 in the thick portion 11 is more preferably 76% or less, and even more preferably 72% or less.

[0089] Furthermore, the small-angle grain boundary ratio B2 of the thin portion 12 is more preferably 76% or less, and even more preferably 72% or less.

[0090] Furthermore, the ratio of small-angle grain boundaries B1 / B2 is preferably in the range of 0.85 < B1 / B2 < 1.15, and more preferably in the range of 0.90 < B1 / B2 < 1.10.

[0091] (Area ratio of crystals with a crystal orientation within 10° relative to the Goss orientation {011}<100>)

[0092] Crystals with a Goss orientation {011}<100> are less prone to dislocation accumulation, thus suppressing atomic diffusion and recovery caused by dislocation movement at high temperatures, thereby improving heat resistance. Furthermore, since the thick portion 11 and the thin portion 12 are used at the same temperature, it is required that the heat resistance of the thick portion 11 and the thin portion 12 is not significantly different.

[0093] Furthermore, the aforementioned Goss orientation {011}〈100〉 does not occur during the usual rolling or heat treatment of copper materials, but can be formed through profile rolling and subsequent processing and heat treatment.

[0094] In this embodiment, the area ratio of the crystal having a crystal orientation within 10° relative to the Goss orientation {011}<100> is set to 1% or more in both the thick portion 11 and the thin portion 12.

[0095] Furthermore, the area ratio of crystals in the thick portion 11 and the thin portion 12 having a crystal orientation of 10° or less relative to the Goss orientation {011}<100> is preferably 1.4% or more, more preferably 1.8% or more, and even more preferably 2.2% or more.

[0096] (Conductivity)

[0097] The copper alloy profiled strip 10 of this embodiment has a conductivity of 48% IACS or higher. By setting the conductivity to 48% IACS or higher, heat generation during energization can be suppressed, making it suitable for use as a component in electronic and electrical equipment such as terminals, busbars, lead frames, and heat sinks.

[0098] Here, the conductivity is preferably 53% IACS or higher, more preferably 58% IACS or higher, even more preferably 63% IACS or higher, and even more preferably 75% IACS or higher.

[0099] Although there are no specific limitations, the conductivity can be below 102.5% IACS, below 102% IACS, or below 101.5% IACS.

[0100] (Heat resistance temperature)

[0101] In the copper alloy profiled strip 10 of this embodiment, it is preferable that the heat resistance temperature T1 of the thick portion 11 is 260°C or higher, and the heat resistance temperature T2 of the thin portion 12 is 240°C or higher. By setting the heat resistance temperature as described above, sufficient heat resistance can be ensured.

[0102] Furthermore, in the copper alloy profiled strip 10, the thick portion 11 and the thin portion 12 are often used under the same temperature conditions. Therefore, the heat resistance temperature T1 of the thick portion 11 and the heat resistance temperature T2 of the thin portion 12 are preferably close values, and the ratio T1 / T2 of the heat resistance temperature T1 of the thick portion 11 to the heat resistance temperature T2 of the thin portion 12 is preferably 0.9 < T1 / T2 < 1.25.

[0103] Here, the heat resistance temperature T1 of the thick portion 11 is more preferably 280°C or higher, more preferably 300°C or higher, and even more preferably 320°C or higher.

[0104] Furthermore, the heat resistance temperature T2 of the thin part 12 is more preferably 260°C or higher, more preferably 280°C or higher, and even more preferably 300°C or higher.

[0105] Furthermore, the ratio of heat resistance temperature T1 / T2 is more preferably in the range of 0.92 < T1 / T2 < 1.20.

[0106] (Vickers hardness)

[0107] In the copper alloy profiled strip 10 of this embodiment, when the Vickers hardness H1 of the thick portion 11 is 70Hv or higher and the Vickers hardness H2 of the thin portion 12 is 75Hv or higher, the strength can be ensured, making it particularly suitable as a raw material for components of electronic and electrical equipment.

[0108] Furthermore, when the difference in Vickers hardness between the thick portion 11 and the thin portion 12 is large, material deformation may occur during the stamping process when manufacturing components for electronic and electrical equipment, especially terminals, busbars, lead frames, and heat sinks. Therefore, the Vickers hardness H1 of the thick portion 11 and the Vickers hardness H2 of the thin portion 12 are preferably close values, and the ratio H1 / H2 of the Vickers hardness H1 of the thick portion 11 to the Vickers hardness H2 of the thin portion 12 is preferably 0.7 < H1 / H2 < 1.2.

[0109] Here, the Vickers hardness H1 of the thick portion 11 is more preferably 72Hv or higher, and even more preferably 74Hv or higher.

[0110] Furthermore, the Vickers hardness H2 of the thin portion 12 is more preferably 77Hv or higher, and even more preferably 79Hv or higher.

[0111] Furthermore, the Vickers hardness ratio H1 / H2 is more preferably in the range of 0.8 < H1 / H2 < 1.1.

[0112] Next, refer to Figure 2 The flowchart shown illustrates the manufacturing method of the copper alloy profiled strip 10 of this embodiment, which is configured in this way.

[0113] (Melting and casting process S01)

[0114] First, the aforementioned elements are added to molten copper obtained by melting copper raw materials to adjust the composition, thereby creating a copper alloy molten liquid. Furthermore, elemental substances or master alloys can be used when adding various elements. Moreover, raw materials containing the aforementioned elements can be melted together with copper raw materials. Additionally, recycled materials and waste materials using this alloy can also be used.

[0115] Here, the preferred copper raw material is so-called 4NCu with a purity of 99.99% by mass or higher, or so-called 5NCu with a purity of 99.999% by mass or higher.

[0116] During melting, in order to suppress the oxidation of Mg and reduce the hydrogen concentration, it is preferable to melt in an inert gas atmosphere (such as Ar gas) with low vapor pressure of H2O, and to limit the holding time during melting to a minimum.

[0117] Then, the molten copper alloy with adjusted composition is poured into a mold to produce an ingot. Furthermore, considering mass production, continuous casting or semi-continuous casting is preferred.

[0118] (Homogenization and solution treatment process S02)

[0119] Next, a heat treatment is performed to homogenize and solution-solidify the obtained ingot. Sometimes, intermetallic compounds, primarily composed of Cu and Mg, are present inside the ingot. These intermetallic compounds are generated during solidification due to Mg segregation and concentration. Therefore, to eliminate or reduce these segregations and intermetallic compounds, a heat treatment is performed, heating the ingot to 300°C or higher but below 1080°C, thereby allowing Mg to diffuse uniformly within the ingot or to dissolve Mg in the parent phase. Furthermore, it is preferable to perform this homogenization and solution-solidification process (S02) in a non-oxidizing or reducing atmosphere.

[0120] Here, when the heating temperature is below 300°C, solidification will be incomplete, and many intermetallic compounds mainly composed of Cu and Mg may remain in the parent phase. On the other hand, if the heating temperature exceeds 1080°C, some of the copper raw material will become liquid, and the microstructure and surface state may become uneven. Therefore, the heating temperature is set in the range of above 300°C and below 1080°C.

[0121] Furthermore, to improve the efficiency of rough rolling and the homogenization of the microstructure, as described later, hot working can be performed after the aforementioned homogenization and solution treatment steps S02. In this case, the processing method is not particularly limited, and methods such as rolling, drawing, extrusion, groove rolling, forging, and stamping can be used. Moreover, the hot working temperature is preferably in the range of 300°C or higher and 1080°C or lower.

[0122] (Rough machining process S03)

[0123] Rough machining is performed to form a specified shape. While the temperature conditions in this rough machining step S03 are not particularly limited, to suppress recrystallization or improve dimensional accuracy, it is preferably set within the range of -200°C to 200°C, which is typically used for cold rolling or warm rolling, and particularly preferably at room temperature. Regarding the machining rate, 20% or more is preferred, and more preferably 30% or more. Furthermore, the machining method is not particularly limited; for example, rolling, drawing, extrusion, groove rolling, forging, stamping, etc., can be used.

[0124] In addition, the roughing process S03 and the intermediate heat treatment process S04 described later can be performed repeatedly.

[0125] (Intermediate heat treatment process S04)

[0126] After the roughing process S03, heat treatment is performed to soften the material or form a recrystallized structure to improve workability.

[0127] At this point, a short-time heat treatment based on a continuous annealing furnace is preferred, as the addition of Ag can prevent the localization of Ag segregation towards grain boundaries.

[0128] There are no particular restrictions on the heat treatment conditions, but it is usually carried out in the range of 200°C to 1000°C.

[0129] (Mechanical surface treatment process S05)

[0130] After the intermediate heat treatment step S04, a mechanical surface treatment is performed. The mechanical surface treatment is a process that applies compressive stress to the vicinity of the surface. By combining it with the heat treatment step S07 before finishing described later, the Goss orientation {011}〈100〉 can be improved, thereby improving the heat resistance.

[0131] Mechanical surface treatment can employ a variety of commonly used methods, such as shot peening, sandblasting, grinding, polishing, polishing and grinding, grinding machine grinding, sandpaper grinding, tension straightening machine treatment, and light rolling with a low reduction rate per pass (a reduction rate of more than 1% and less than 10% per pass, repeated more than three times).

[0132] (Irregular shape rolling process S06)

[0133] In profile rolling, a flat die with concave and convex surfaces and a roll that moves back and forth along the forming surface opposite to the forming surface are used to perform profile cold rolling on the material after the mechanical surface treatment process S05, thereby obtaining a coarse profile strip with thick and thin sections arranged in the width direction.

[0134] Furthermore, since the reduction rate of the machining is set within the range of 5% to 90%, Goss orientation is easily formed in the heat treatment process S07 before finishing. The reduction rate of the machining is further preferably within the range of 10% to 85%, and even more preferably within the range of 15% to 80%.

[0135] Furthermore, since the ratio of the thickness of the thick portion to the thickness of the thin portion is set to 6 or less, the ratio of the small-angle grain boundary and subgrain boundary lengths of the thick portion 11 and the thin portion 12, i.e., the small-angle grain boundary ratio B = L, can be achieved in the heat treatment process S07 before finishing. LB / (L LB +L HB By setting the ratio B1 / B2 to 0.8 < B1 / B2 < 1.2, the Vickers hardness ratio H1 / H2 of the thick portion 11 and the thin portion 12 can be set to 0.7 < H1 / H2 < 1.2. Furthermore, the ratio of the thickness of the thick portion to the thickness of the thin portion is more preferably 5 or less.

[0136] (Heat treatment process S07 before finishing)

[0137] Next, a recrystallized structure is formed by heat treatment after the profile rolling process S06, thereby achieving a Goss orientation. Furthermore, recrystallization reduces the small-angle grain boundary ratio B. Further, the microstructures of the thick portion 11 and the thin portion 12 are made similar.

[0138] In the heat treatment step S07 prior to finishing, in order to eliminate the strain difference between the thick and thin sections introduced by the profile rolling process S06, and thus achieve a uniform microstructure through recrystallization and subsequent grain growth, a constant heating rate and a sufficiently long heat treatment time are required. Therefore, batch annealing is preferred for heat treatment. Regarding the heat treatment conditions, a heat treatment temperature of 250°C or higher and 650°C or lower is preferred, a heating rate of 500°C / h or lower is preferred, and a heat treatment time of 1 hour or higher and 100 hours or lower is preferred.

[0139] (Fine machining process S08)

[0140] After the heat treatment process S07 prior to finishing, finishing is performed. This is carried out by finishing based on rolls composed of stepped rolls and flat rolls.

[0141] In addition, in order to set the Vickers hardness H1 of the thick portion 11 to 70Hv or more and the Vickers hardness H2 of the thin portion 12 to 75Hv or more, the processing rate is preferably 5% or more, and more preferably 8% or more.

[0142] On the other hand, if the processing rate is too high, the ratios of small-angle grain boundaries B1 and B2 will increase, and the area ratio of the Goss orientation, which is a recrystallized structure, will also decrease. Therefore, the processing rate is preferably 50% or less, and more preferably 45% or less.

[0143] (Low-temperature annealing process S09)

[0144] After the finishing process S08, low-temperature annealing is performed as needed. Through this low-temperature annealing process S09, the ratio of small-angle grain boundaries can be reduced by removing and restoring residual stress.

[0145] In this low-temperature annealing process S09, it is preferable to set the annealing temperature to a range of 100°C or higher and 600°C or lower, and to set the holding time at the annealing temperature to a range of 0.1 seconds or higher and 24 hours or lower. Furthermore, a longer heat treatment time is sufficient when the heat treatment temperature is lower, while a shorter heat treatment time is sufficient when the heat treatment temperature is higher.

[0146] In the low-temperature annealing process S09, if the annealing temperature is below 100°C or the holding time at the annealing temperature is less than 0.1 seconds, it may not be possible to obtain a sufficient stress relief effect. On the other hand, recrystallization may occur when the annealing temperature exceeds 600°C, and when the holding time at the annealing temperature exceeds 24 hours, it will only lead to increased costs.

[0147] In addition, in this embodiment, a straightening process based on a tension straightening machine or the like can be added after the low-temperature annealing process S09.

[0148] Furthermore, a metal plating layer can be formed on the surface of the copper alloy profiled strip 10 in this embodiment. Additionally, as the metal plating layer, for example, Sn plating, Ag plating, Ni plating, Au plating, Pd plating, Rh plating, etc., can be applied.

[0149] Through the above processes, the copper alloy profiled strip 10 of this embodiment can be manufactured.

[0150] In the copper alloy profiled strip 10 of this embodiment, configured as described above, since the Mg content is in the range of more than 10 ppm by mass and less than 1.2% by mass, and the P content is in the range of more than 0 ppm by mass and less than 200 ppm by mass, the heat resistance can be sufficiently improved by the solid dissolution of Mg in the copper matrix phase.

[0151] Furthermore, since its conductivity is above 48% IACS, it can suppress heat generation when energized, making it suitable as a raw material for electronic and electrical equipment components such as terminals, busbars, lead frames, and heat dissipation substrates.

[0152] Furthermore, the heat resistance temperature T1 of the thick part 11 is above 260°C, and the heat resistance temperature T2 of the thin part 12 is above 240°C, and 0.9 < T1 / T2 < 1.25. Therefore, the heat resistance is sufficiently excellent, and the difference in heat resistance between the thick part 11 and the thin part 12 is small, so it can be used stably even in high-temperature environments.

[0153] Furthermore, the small-angle grain boundary ratios B1 and B2 of the thick portion 11 and the thin portion 12 are each less than 80%, and the ratio of the small-angle grain boundary ratios B1 / B2 is 0.8 < B1 / B2 < 1.2. The crystal structure is controlled such that the area ratio of crystals with a crystal orientation of less than 10° relative to the Goss orientation {011} < 100> is more than 1% in both the thick portion and the thin portion. Therefore, recovery or recrystallization caused by dislocation movement is less likely to occur, and the heat resistance of the thick portion 11 and the thin portion 12 can be sufficiently improved.

[0154] In the copper alloy profiled strip 10 of this embodiment, when the unavoidable impurities are S content of 10 ppm by mass or less, Se content of 5 ppm by mass or less, Te content of 5 ppm by mass or less, Sb content of 5 ppm by mass or less, Bi content of 5 ppm by mass or less, and As content of 5 ppm by mass or less, and the total content of S, Se, Te, Sb, Bi and As is 24 ppm by mass or less, since the content of the elements that form compounds with Mg, namely S, Se, Te, Sb, Bi and As, is controlled to be low, Mg can be reliably dissolved, thereby further reliably improving the heat resistance.

[0155] Furthermore, in the copper alloy profiled strip 10 of this embodiment, when the content of Ag is in the range of 5 ppm by mass or more and 20 ppm by mass or less, Ag will segregate near the grain boundary. By suppressing grain boundary diffusion through Ag, the heat resistance temperature can be further reliably improved.

[0156] Furthermore, in the copper alloy profiled strip 10 of this embodiment, the Vickers hardness H1 of the thick portion 11 is 70Hv or higher, the Vickers hardness H2 of the thin portion 12 is 75Hv or higher, and when 0.7 < H1 / H2 < 1.2, the strength is excellent, and the strength difference between the thick portion 11 and the thin portion 12 is small, so it can be used stably.

[0157] Furthermore, when a metal plating layer is formed on the surface of the copper alloy profiled strip 10 in this embodiment, various properties can be imparted to the surface, making it particularly suitable as a raw material for electronic and electrical equipment components such as terminals, busbars, and heat dissipation substrates.

[0158] Furthermore, the electronic and electrical equipment components (terminals, busbars, lead frames, heat sinks, etc.) of this embodiment are made of the aforementioned copper alloy profiled strip 10, thus enabling them to exhibit excellent characteristics even in high-temperature environments.

[0159] The copper alloy profiled strip 10 and electronic and electrical equipment components (terminals, busbars, lead frames, heat dissipation substrates, etc.) of the embodiments of the present invention have been described above. However, the present invention is not limited thereto, and appropriate modifications can be made without departing from the technical concept of the present invention.

[0160] For example, in the above embodiments, an example of a method for manufacturing copper alloy profiled strip 10 has been described, but the method for manufacturing copper alloy profiled strip 10 is not limited to the method described in the embodiments, and existing manufacturing methods may also be appropriately selected.

[0161] Furthermore, in this embodiment, Figure 1The shaped strip shown is given as an example and is illustrated, but it is not limited to this and can be shaped strip with other cross-sectional shapes.

[0162] Example

[0163] The results of the confirmation experiments conducted to verify the effectiveness of the present invention will be described below.

[0164] Raw materials consisting of pure copper with a purity of 99.999% by mass or higher obtained by zone refining were loaded into a high-purity graphite crucible and subjected to high-frequency melting in an atmosphere furnace set with Ar gas atmosphere.

[0165] The compositions shown in Tables 1 and 2 were prepared by using 0.1% by mass of various master alloys as described below in the obtained molten copper, and then cast into an insulating material (ISOWOOL) mold to produce an ingot. The master alloys were manufactured using high-purity copper with a purity of 99.9999% by mass or higher and pure metals with a purity of 2% by mass or higher. Furthermore, the ingot size was set to approximately 30 mm in thickness, approximately 60 mm in width, and approximately 150–200 mm in length.

[0166] The obtained ingots are heated for 1 hour in an Ar gas atmosphere at various temperature conditions, the surface is ground to remove the oxide coating, and then cut into specified sizes.

[0167] The thickness was then adjusted appropriately to achieve the final thickness, and the specimens were cut. Each cut specimen was rough rolled at room temperature, followed by intermediate heat treatment.

[0168] Next, these samples underwent a mechanical surface treatment process using the methods described in Tables 3 and 4.

[0169] Additionally, polish and grind using #1000 abrasive paper.

[0170] The tension straightener uses a tension straightener equipped with multiple φ16mm rollers, at a speed of 100N / mm. 2 Line tension is implemented.

[0171] Regarding light rolling (rolling with a low reduction rate per pass), the final 3 passes are implemented with a reduction rate of 4% per pass.

[0172] Then, with the thicknesses of the thick and thin parts being the values ​​recorded in Tables 3 and 4 respectively, a stepped profile rolling process was performed using a flat die and rolls that moved back and forth along the forming surface opposite to the forming surface of the die.

[0173] Then, heat treatment prior to finishing was performed under the conditions described in Tables 3 and 4.

[0174] Subsequently, the strips for performance evaluation with a thickness and a width of approximately 60 mm, as shown in Tables 3 and 4, were manufactured by finishing under the conditions described in Tables 3 and 4, and by low-temperature annealing except for a portion of the samples.

[0175] The strip used to evaluate the obtained characteristics was evaluated in the following manner.

[0176] (Composition Analysis)

[0177] Measurement samples were collected from the obtained ingots. Mg was measured by inductively coupled plasma atomic emission spectrometry, and other elements were measured using glow discharge mass spectrometry (GD-MS).

[0178] In addition, measurements were taken at both the center and the end of the sample in the width direction, with the measurement at the higher position being taken as the content of the sample. The results confirmed the composition shown in Tables 1 and 2.

[0179] (Small-angle grain boundary ratio)

[0180] Using the rolling surface, i.e., the ND (Normal direction) surface, as the observation surface, the small dip angle grain boundary ratios B1 and B2 of the thick and thin parts are determined by using an EBSD measurement device and OIM analysis software in the following manner.

[0181] After mechanical polishing using water-resistant abrasive paper and diamond abrasive, fine polishing was performed using a colloidal silica solution. Then, using an EBSD measurement device (FEI Quanta FEG 450, EDAX / TSL (now AMETEK) OIM Data Collection) and analysis software (EDAX / TSL (now AMETEK) OIM DataAnalysis ver. 7.3.1), at an electron beam accelerating voltage of 15 kV, at a depth of 10000 μm... 2 In the above measured areas, measurement points with a CI value below 0.1 were excluded by using a measurement interval of 0.25 μm. Orientation difference analysis was performed on each grain, and measurement points with an orientation difference greater than 15° between adjacent measurement points were defined as grain boundaries. The average grain size A was calculated using the data analysis software OIM and through area fraction. Subsequently, measurements were performed with a measurement interval less than 1 / 10th of the average grain size A, covering more than 1000 grains, at multiple fields of view, resulting in a measurement area of ​​10000 μm. 2Of the measured areas above, measurement points with a CI value below 0.1 as analyzed by the OIM data analysis software were excluded. Measurement points with an orientation difference of 2° or more but less than 15° between adjacent points were designated as small-angle grain boundaries and subgrain boundaries, with their length defined as L. LB Measurement points exceeding 15° are designated as large-angle grain boundaries, with their length defined as L. HB Thus, the ratio of small-angle grain boundaries B = L, which is the ratio of the lengths of small-angle grain boundaries and subgrain boundaries in the total grain boundary, was determined. LB / (L LB +L HB ).

[0182] (Goss orientation)

[0183] When performing the above-mentioned small-angle grain boundary and subgrain boundary length ratio measurements, the orientation analysis of each grain is also performed to determine whether each analysis point is the target Goss orientation (within 10° of the ideal orientation), thereby calculating the Goss orientation ratio (area ratio of crystal orientation) of the measurement area.

[0184] (Heat resistance temperature)

[0185] Regarding the heat resistance temperature, based on the isochronous softening curve of Vickers hardness obtained after 1 hour of heat treatment according to JCBA T325:2013 of the Japan Copper and Brass Association, the heating temperature at which the hardness reaches 80% of the original hardness was determined, and the evaluation was conducted. Furthermore, the Vickers hardness was measured on the rolled surface. The evaluation results are shown in Tables 5 and 6.

[0186] (Vickers hardness)

[0187] According to the micro Vickers hardness test method specified in JIS-Z2244, the Vickers hardness was measured on the surface of the strip used for characteristic evaluation, i.e., the ND (Normal Direction) surface, with a test load of 0.98 N. The evaluation results are shown in Tables 3 and 4.

[0188] (Conductivity)

[0189] Test pieces with a width of 10 mm and a length of 60 mm were collected from the strip used for characteristic evaluation, and the resistance was determined using the 4-terminal method. Furthermore, the dimensions of the test pieces were measured using a micrometer, and the volume of the test pieces was calculated. The conductivity was then calculated based on the measured resistance and volume. The test pieces were collected with their length parallel to the rolling direction of the strip used for characteristic evaluation. The evaluation results are shown in Tables 5 and 6.

[0190] [Table 1]

[0191]

[0192] [Table 2]

[0193]

[0194]

[0195]

[0196] [Table 5]

[0197]

[0198] [Table 6]

[0199]

[0200] In Comparative Example 1, the heat resistance temperature was lower and the heat resistance was insufficient because the Mg content was less than that of the present invention.

[0201] In Comparative Example 2, the Mg content exceeded the range of the present invention, resulting in lower conductivity.

[0202] In Comparative Example 3, the P content exceeded 200 ppm by mass, the heat resistance temperature was low, and the heat resistance was insufficient.

[0203] In Comparative Example 4, the ratio of small-angle grain boundaries exceeded 80%, the heat resistance temperature was low, and the heat resistance was insufficient.

[0204] In Comparative Example 5, the area ratio of the Goss orientation was less than 1%, the heat resistance temperature was low, and the heat resistance was insufficient.

[0205] In Comparative Example 6, the ratio of the small-angle grain boundary ratio B1 of the thick portion to the small-angle grain boundary ratio B2 of the thin portion, B1 / B2, is outside the scope of the present invention, and the ratio of the heat resistance temperature T1 of the thick portion to the heat resistance temperature T2 of the thin portion, T1 / T2, is outside the scope of the present invention, thus causing a deviation in heat resistance.

[0206] In contrast, in Examples 1 to 30 of the present invention, it was confirmed that the heat resistance of both the thick and thin portions was improved in a balanced manner.

[0207] Based on the above, it is confirmed that, according to the present invention, a copper alloy profiled strip can be provided that exhibits characteristics such as strength and heat resistance that are not significantly different between the thick and thin portions and can be used stably in high-temperature environments.

[0208] Industrial availability

[0209] It can provide a copper alloy profiled strip with properties such as strength and heat resistance that are not easily different between thick and thin sections and can be used stably in high-temperature environments, as well as electronic and electrical equipment components, terminals, busbars, lead frames, and heat dissipation substrates made of the copper alloy profiled strip.

[0210] Symbol Explanation

[0211] 10 Copper alloy profiled strip

[0212] 11 thick part

[0213] 12 Thin section

[0214] Thickness of t1 thick part 11

[0215] Thickness of t2 thin part 12

Claims

1. A copper alloy profiled strip, having thick and thin sections of varying thicknesses on a cross-section orthogonal to its length direction, characterized in that... The copper alloy profiled strip has a Mg content in the range of more than 10 ppm by mass and less than 1.2% by mass, a P content in the range of more than 0 ppm by mass and less than 200 ppm by mass, and the remainder is Cu and unavoidable impurities. Conductivity above 48% IACS The heat resistance temperature T1 of the thick portion is 260°C or higher, and the heat resistance temperature T2 of the thin portion is 240°C or higher, and 0.9 < T1 / T2 < 1.

25. Using the EBSD method, in the rolled surface, measurement points with a CI value below 0.1 are excluded at measurement intervals of 0.25 μm. This applies to a 10000 μm... 2 The above measurement areas were used to analyze the orientation difference of each grain. Grain boundaries were defined between adjacent measurement points with an orientation difference of 15° or more. The average grain size A was calculated using area fractions. Measurements were performed at intervals less than 1 / 10 of the average grain size A, covering more than 1000 grains, with a total field of view of 10000 μm. 2 Of the measured areas above, measurement points with a CI value below 0.1 as analyzed by the data analysis software OIM were excluded. The length of the small-angle grain boundaries and subgrain boundaries between adjacent measurement points with an orientation difference of 2° or more but less than 15° was defined as L. LB The length of the large-angle grain boundary between adjacent measurement points with an orientation difference exceeding 15° is defined as L. HB And let the length ratio of the small-angle grain boundary and the subgrain boundary be defined as the small-angle grain boundary ratio B = L. LB / (L LB +L HB When the ratio of small-angle grain boundaries B1 in the thick portion is 80% or less, and the ratio of small-angle grain boundaries B2 in the thin portion is 80% or less, and 0.8 < B1 / B2 < 1.2, The area ratio of crystals having a crystal orientation within 10° relative to the Gaussian orientation {011}<100> is 1% or more in both the thick and thin portions.

2. The copper alloy profiled strip according to claim 1, characterized in that, Of the unavoidable impurities, the content of S is less than 10 ppm by mass, the content of Se is less than 5 ppm by mass, the content of Te is less than 5 ppm by mass, the content of Sb is less than 5 ppm by mass, the content of Bi is less than 5 ppm by mass, the content of As is less than 5 ppm by mass, and the total content of S, Se, Te, Sb, Bi and As is less than 24 ppm by mass.

3. The copper alloy profiled strip according to claim 1 or 2, characterized in that, The content of Ag is in the range of 5 ppm by mass and 20 ppm by mass.

4. The copper alloy profiled strip according to any one of claims 1 to 3, characterized in that, The Vickers hardness H1 of the thick portion is 70Hv or higher, and the Vickers hardness H2 of the thin portion is 75Hv or higher, and 0.7 < H1 / H2 < 1.

2.

5. The copper alloy profiled strip according to any one of claims 1 to 4, characterized in that, The surface of the copper alloy profiled strip has a metal plating layer.

6. A component for electronic and electrical equipment, characterized in that, The electronic and electrical equipment components are made of copper alloy profiled strips as described in any one of claims 1 to 5.

7. A terminal, characterized in that, The terminal is made of a copper alloy profiled strip as described in any one of claims 1 to 5.

8. A busbar, characterized in that, The busbar is made of any one of the copper alloy profiled strips according to claims 1 to 5.

9. A lead frame, characterized in that, The lead frame is made of copper alloy profiled strip as described in any one of claims 1 to 5.

10. A heat dissipation substrate, characterized in that, The heat dissipation substrate is made of copper alloy profiled strip as described in any one of claims 1 to 5.

Citation Information

Patent Citations

  • Method for producing copper alloy sheet with deformed cross section

    JP2007039735A

  • Copper alloy strip material for terminal and its manufacturing method

    JP2009009887A

  • Copper rolled sheet and component for electronic and electrical device

    JP2016056414A

  • Copper alloy for electronic and electrical parts, planar row material and row material having deformed cross section, and lead frame formed by the planar row material or row material having deformed cross section

    JP2001279348A

  • Copper alloy deformed bar stock and method for producing the same

    JP2010100911A